Biochar e fertilizantes especiais no crescimento inicial da cultura do milho - Franco, Miguel Henrique Rosa Franco (2019)
The fertilizer industry has tested various types of products aimed at increasing the efficiency of nutrients. Based on these assumptions, the objective of this study was to compare in a greenhouse in the corn crop, the agronomic efficiency of organic fertilizers, organomineral and with addition of polymers in relation to conventional mineral fertilizer. For both, two experiments were carried out under greenhouse conditions at the Federal University of Uberlândia. The first experiment was composed by the evaluation of the agronomic efficiency of organomineral (OM) fertilizers (filter cake and biochar), their mixture with humic substances (SH), and the comparison of these with the fertilization with conventional mineral fertilizer in the corn. For this purpose, the experiment was conducted in a randomized complete block design, in a 7x4 + 1 factorial scheme, with four replications per treatment. The first factor consists of seven different sources of fertilizer (organic compound filter cake, biochar organic compound, OM filter cake base, OM biochar based, OM filter cake base + SH , OM based on biochar + SH and conventional mineral), the second factor served by the use of different doses based on levels of nitrogen (40, 80, 120 and 160 kg ha -1 of N); and finally the addition of an absolute control without applications of fertilizer. In general, the treatments OM filter cake, filter cake compound and OM biochar were those that obtained a better index of agronomic efficiency when compared to the mineral. The second experiment was composed by the evaluation of the agronomic efficiency of special fertilizers based on mineral with addition of polymer, pelletized organomineral (OM) fertilizers (filter cake and biochar) and its mixture with humic substances (SH), on initial growth of corn crop, comparing the results obtained in the application of these with the application of conventional mineral fertilizer. The experimental design consisted of a randomized complete block design in a 7x4 + 1 factorial scheme, with four replications per treatment. The first factor consists by seven different sources (organic compound filter cake, organic compound biochar, OM filter cake, organomeral biochar, OM filter cake + SH, mineral with polymer and conventional mineral), the second factor answered by the use of diferente doses based on level of nitrogen (60, 120, 180 and 240 kg ha-1 of N), and to stop the addition of an absolute control without the application of fertilizers. In this, the OM fertilizers filter cake, OM biochar, OM pie with addition of humic substances and mineral with polymer were more efficient than the mineral fertilizer.